Osteomyelitis of the face: Clinicopathological study of a 15 year old database at the university hospital of yaoundé - Ntep Ntep David Bienvenue; Bola Siafa Antoine; Kenna Ernest; Zilefac Ngokwe Brian; Gimel Stéphane Nokam Kamdem; Bengondo Messanga Charles (Elsevier, 2021)
Context: Facial osteomyelitis is an inflammatory process of the bones of the face. It is common in poor countries as a result of a weak health care system. The diagnosis and management of this pathology is complex in our context because of poor medical equipment. Aims: The objective of this study was to establish a nosological framework for facial osteomyelitis. Settings: and Design: This was a retrospective study of facial osteomyelitis collected in the Odontostomatology/Maxillo-Facial and Otolaryngology/Cervico-Facial Surgery Departments of the Yaoundé University Hospital over a period of 15 years. Methods and material: All patients diagnosed with facial osteomyelitis by one of the physicians of the above departments mentioned services were included. An epidemiological record (sex, age, ethnic origin, risk factors, clinical, origin of the disease, imaging and biology) was collected for each patient. Osteomyelitis was classified according to the Zurich classification. Statistical analysis used: Descriptive statistics were performed and the Fisher test was used to indicate differences in radiographic characteristics between the types of facial osteomyelitis. A p-value of less than 0.05 was considered to indicate statistical significance. Results: Of the ninety-nine facial osteomyelitis, eleven (12.3%) were acute and seventy-eight (87.6%) were chronic osteomyelitis, nine of which were primary and sixty-nine secondary. The presence of suppuration, fistula and or denudation were the prerogative of secondary chronic osteomyelitis. Heterogeneous spinal fibrosis and pseudodysplastic hyperplasia were pathognomonic of primary chronic osteomyelitis. Conclusion: These results suggest that the main differences between the types of osteomyelitis reside: in the duration of disease progression; whether or not suppuration/stripping and fistula are present; the presence or absence of mixed sclerosis, sequestration and fistula heterogeneous spinal cord fibrosis and pseudodysplastic hyperplasia.